2014
DOI: 10.1002/dvdy.24147
|View full text |Cite
|
Sign up to set email alerts
|

Endoderm‐specific deletion of Tbx1 reveals an FGF‐independent role for Tbx1 in pharyngeal apparatus morphogenesis

Abstract: Background The T-box transcription factor Tbx1, is essential for the normal development of multiple organ systems in the embryo. One of the most striking phenotypes in Tbx1−/− embryos is the failure of the caudal pharyngeal pouches to evaginate from the foregut endoderm. Despite considerable interest in the role of Tbx1 in development, the mechanisms whereby Tbx1 controls caudal pouch formation have remained elusive. In particular, the question as to how Tbx1 expression in the pharyngeal endoderm regulates pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 47 publications
(71 reference statements)
7
24
1
Order By: Relevance
“…In mice, Tbx1 expression appears to mark nascent pouch regions while the related Tbx2 and Tbx3 factors are expressed in inter-pouch zones of endoderm [21,22]. However, Tbx1 was found to be dispensable for early segmental Fgf activity in zebrafish and endodermal Fgf activity in mice [15,23], instead having important requirements in the mesoderm for the subsequent morphogenesis of endodermal segments as discussed below.…”
Section: Segmentation Of the Pharyngeal Endoderm Into Pouchesmentioning
confidence: 99%
“…In mice, Tbx1 expression appears to mark nascent pouch regions while the related Tbx2 and Tbx3 factors are expressed in inter-pouch zones of endoderm [21,22]. However, Tbx1 was found to be dispensable for early segmental Fgf activity in zebrafish and endodermal Fgf activity in mice [15,23], instead having important requirements in the mesoderm for the subsequent morphogenesis of endodermal segments as discussed below.…”
Section: Segmentation Of the Pharyngeal Endoderm Into Pouchesmentioning
confidence: 99%
“…Global inactivation of tbx1 and restoration in the PE failed to rescue pouch defects in zebrafish mutant larvae (Choe and Crump, 2014). In contrast, inactivation of Tbx1 in the PE results in failed segmentation of the distal PA in mice (Arnold et al, 2006a;Jackson et al, 2014). Cell proliferation is not affected when Tbx1 is inactivated in the endoderm using Sox17 2A-iCre/+ , but pouches do not form in these mutant embryos regardless (Jackson et al, 2014).…”
Section: Tbx1 Functions To Promote Invagination and Stratification Cementioning
confidence: 95%
“…Previous studies have shown that global or endoderm inactivation of Tbx1 resulted in failed segmentation of PA2-PA6 (Arnold et al, 2006b;Jackson et al, 2014;Jerome and Papaioannou, 2001;Lindsay et al, 2001;Merscher et al, 2001). To test the mechanism by which segmentation was disrupted, Tbx1 -/mutant embryos were generated and immunofluorescence with antibodies to Ecadherin and ZO-1 was performed on coronal tissue sections.…”
Section: Tbx1 In the Pa Endoderm Initiates Invagination And Stratificmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tbx1 −/− mice and mice lacking Tbx1 specifically from the endoderm, pharyngeal pouches fail to evaginate from the foregut endoderm. Loss of Fgf3 and Fgf8 from the pharyngeal endoderm only partially disrupted pouch morphogenesis indicating that Fgf signaling is not required for pouch formation (Jackson, Kasah, Mansour, Morrow, & Basson, ). However , Fgf8 is required, together with Fgf3 , for segmentation of the pharyngeal endoderm into pouches in zebrafish (Crump, Maves, Lawson, Weinstein, & Kimmel, ).…”
Section: Ncc Migrationmentioning
confidence: 99%